2021
DOI: 10.1016/j.celrep.2021.109466
|View full text |Cite
|
Sign up to set email alerts
|

The Nrf2-Keap1 pathway is activated by steroid hormone signaling to govern neuronal remodeling

Abstract: Highlights d The conserved Nrf2-Keap1 pathway governs dendrite pruning of mechanosensory neurons d Nrf2-Keap1 pathway is activated by ecdysone signaling prior to dendrite pruning d Nrf2-Keap1 pathway is activated via a cytoplasmic-tonuclear translocation of CncC d Nrf2-Keap1 pathway regulates pruning via proteasomal but not antioxidant function

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 74 publications
(111 reference statements)
1
17
0
Order By: Relevance
“…In a previous study, lovastatin treatment provides neuroprotection in the G2019S-induced PD model, also through the Akt/Nrf2 pathway ( Lin et al, 2016b ). As activation of neuronal Nrf2 plays a nonconventional role in promoting developmental dendrite pruning ( Chew et al, 2021 ), it remains interesting to further study the cell types that mediate the action of lovastatin. By genetically manipulating the G2019S fly model, we have shown that WGE-induced Nrf2 activation in glia but not in neurons protects dopaminergic neurons from degeneration and ameliorates impaired locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, lovastatin treatment provides neuroprotection in the G2019S-induced PD model, also through the Akt/Nrf2 pathway ( Lin et al, 2016b ). As activation of neuronal Nrf2 plays a nonconventional role in promoting developmental dendrite pruning ( Chew et al, 2021 ), it remains interesting to further study the cell types that mediate the action of lovastatin. By genetically manipulating the G2019S fly model, we have shown that WGE-induced Nrf2 activation in glia but not in neurons protects dopaminergic neurons from degeneration and ameliorates impaired locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…NF-E2-relatedfactor2 (NRF2) plays an important role in regulating the homeostasis of cells and a key factor in oxidoreduction reaction (Zhang et al, 2016;Fan et al, 2017). Relevant studies have shown that when NRF2 is up-regulated in tumors, it is closely related to the poor prognosis of primary malignant brain tumors (Chew et al, 2021); the NRF2-Keap1 system regulates the expression of human antioxidant proteins, which is a typical antioxidant reaction pathway. Fe 2+ is regulated by NRF2.…”
Section: Iron Metabolism Affects the Ferroptosismentioning
confidence: 99%
“…The expression of Sox14 also requires a cooperation between the chromatin remodelling factor Brahma (Brm) and the histone acetyltransferase CREB-binding protein (CBP), which leads to local histone acetylation at the sox14 locus [ 29 ]. Third, Sox14 in turn induces the expression of the F-actin disassembly factor Mical [ 27 , 30 ], the Cullin1-based E3 ubiquitin ligase complex [ 31 ] and activation of the metabolic regulator AMP-activated protein kinase [ 32 , 33 ] and the Nrf2-Keap1 pathway [ 34 ] to promote neuronal pruning. Although some key components of the ecdysone-induced signalling cascade have been identified, the transcriptional regulation machinery of neuronal pruning remains incomplete.…”
Section: Introductionmentioning
confidence: 99%